An investigation of EFL learner’s cultural awareness through literary text encounters - RohmanaWahyu Indah Mala (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
This study discusses how EFL students’ cultural awareness was reinforced through their encounters with diverse literary texts. It covers the understanding of the relationship between culture and literary text and how literary text plays a role in strengthening cultural awareness in students. It is qualitative descriptive research examining EFL students. Observation and interviews were used in the study. The result shows how students perceive the value and meaning of literary works. This study shows that when students were assigned into groups, it reinforced them to speak and discuss more and build their critical thinking through the cultural knowledge combined with their reading of the literature. It is found that cultural awareness can be conveyed by analyzing the text and characters of literary text through meaning construction, interpretation of the text, and discussion about identity and culture. However, it also revealed that cultural awareness in the target and international cultural representation was still lacking.